Keynes, Trouton and the Hector Whaling Company. A personal and professional relationship - Basberg, Bjørn L (Business History, 2017)
John Maynard Keynes’ activities on the stock market are well known. One company in which he bought stocks was the Hector Whaling Company Ltd., London – a comparatively small and little known company founded in 1928. The director of this company was Rupert Trouton. He had worked with Keynes for the Government during the First World War, was his student at Cambridge, and became a close partner in the City from the 1920s and onwards. The reason why Keynes invested in Hector was obviously his association with Rupert Trouton. The first part of this paper explores briefly the development of the Hector Whaling Company and its origins in Norway. The main part analyses the relationship between Trouton and Keynes. The focus is on their co-operation relating to Hector Whaling, but their relationship regarding various other businesses, as well as on the personal level, is also described. The paper is based on studies of the Keynes archives in Cambridge as well as newly available archives of the Hector company. The analysis provides new insights to the more general question on the motivations and decisions behind Keynes’ stock market investments as well as the internationalization of the whaling industry in the 1920s and 30s.
Keywords: Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; økonomi

To hvalfangstentreprenøren - to strategier? - Basberg, Bjørn L (I det lange løp : essays i økonomisk historie tilegnet Fritz Hodne, 1997)
Keywords: Antarktis; Carl Anton Larsen; Christen Christensen; Norge; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalfangststasjoner; hvalkokerier; næringsliv; pelagisk; økonomi